Development of a gait module to complement the 12-item Multiple Sclerosis Walking Scale: a mixed methods study. Issue 2 (June 2018) - Strzok, Sara; Cleanthous, Sophie; Pompilus, Farrah; Cano, Stefan J; Marquis, Patrick; Cohan, Stanley; Goldman, Myla D; Kresa-Reahl, Kiren; Petrillo, Jennifer; Castrillo-Viguera, Carmen; Cadavid, Diego; Chen, Shih-Yin
Background and objective: The 12-item Multiple Sclerosis Walking Scale (MSWS-12) is a patient-reported outcome instrument that quantifies the progressive loss of walking ability from the patient perspective. However, previous psychometric analyses indicated floor and ceiling effects across the multiple sclerosis severity spectrum. This study aimed to address floor effects by creating a gait module that can be used in conjunction with the MSWS-12 for better measurement of treatment benefit in the higher functioning multiple sclerosis population. Methods: We used a step-wise mixed methods study design, with relapsing–remitting multiple sclerosis patients (wave 1, n =88; wave 2, n =30), combining qualitative (concept elicitation and cognitive debriefing interviews) and quantitative (Rasch Measurement Theory) data collection and analytical techniques and consultation interviews with three neurologists specializing in multiple sclerosis. Results: Thirty-seven walking ability concepts were identified, and a five-domain conceptual framework was created. Draft items were generated and refined with patient and neurologist input. Draft items covered gait-related concepts such as dragging, shuffling, limping, tripping and falling. Rasch measurement theory psychometric analysis indicated administering MSWS-12 plus gait items improved measurement precision in targeted populations with better walking ability. Conclusion: Study findings indicate that new gait items could improve sensitivity to detect clinical change in walking ability for higher functioning multiple sclerosis patients.